Noncommutativity and noncentral zero divisors - Howard E. Bell; Abraham A. Klein (International Journal of Mathematics and Mathematical Sciences)
Let R be a ring, Z its center, and D the set of zero divisors. For finite noncommutative rings, it is known that D\Z≠∅. We investigate the size of |D\Z| in this case and, also, in the case of infinite noncommutative rings with D\Z≠∅.